2019
DOI: 10.1021/acs.energyfuels.9b03784
|View full text |Cite
|
Sign up to set email alerts
|

A New Method To Evaluate Reaction Kinetics of Acids with Carbonate Rocks Using NMR Diffusion Measurements

Abstract: In this work, a new method to evaluate the reaction kinetics of different stimulation fluids with carbonate rocks was introduced. NMR diffusion measurements were used to determine the acid diffusion coefficient and the acid tortuous path inside carbonate rocks. Reaction kinetics can also be evaluated using rotating disk apparatus (RDA) in which a disc is rotated in the bulk fluid at different rotational speeds. RDA does not represent the actual, restricted acid diffusion that takes place in the porous media be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…It showed lower removal efficiency compared to EDTA and DTPA at the same conditions. , The NTA chelating agent was also effective in removing the filter cake formed by calcite water- and oil-based drilling fluid in 24 h of soaking time . A polyacidic chelate (NPC) breaker was developed to dissolve the filter cake formed by calcite drilling fluid …”
Section: Chelating Agents As Filter Cake Removersmentioning
confidence: 99%
See 1 more Smart Citation
“…It showed lower removal efficiency compared to EDTA and DTPA at the same conditions. , The NTA chelating agent was also effective in removing the filter cake formed by calcite water- and oil-based drilling fluid in 24 h of soaking time . A polyacidic chelate (NPC) breaker was developed to dissolve the filter cake formed by calcite drilling fluid …”
Section: Chelating Agents As Filter Cake Removersmentioning
confidence: 99%
“…123 A polyacidic chelate (NPC) breaker was developed to dissolve the filter cake formed by calcite drilling fluid. 124 Overall, chelating agent solutions show high performance in different applications of filter cake cleanup processes. Table 4 summarizes the solubility of filter cake in different types of chelating agents.…”
Section: Chelating Agents As Filter Cake Removersmentioning
confidence: 99%
“…A higher Δ value is recommended so that the diffusing molecules experience the geometrical restrictions of the confining space. Elsayed et al 26 proposed a new model that replaces the heterogeneity factor in the equation by Mahmoud and Nasr-El-Din. 54 with diffusive tortuosity.…”
Section: Parallel Platesmentioning
confidence: 99%
“…Currently, the study conducted by Elsayed et al 26 was the only one that suggested measuring the diffusion coefficient of a weak acid using NMR. The measurement was carried out using the approach proposed by Zecca et al 66 and Cott et al 67 The approach was originally used to measure the self-diffusion of nonreactive fluids.…”
Section: Parallel Platesmentioning
confidence: 99%
“…Moreover, special core analysis (SCA) experiments such as wettability, capillary pressure, and clay minerals analysis can be determined using NMR (Al-Garadi et al 2022;Connolly et al 2017;Elsayed et al 2020a;Freedman et al, 2003a;Newgord et al 2020;Tandon et al 2020;Tandon and Heidari 2018;Worden and Morad 1999). Numerous EOR methods including acid and fracture stimulation, thermochemical fluids for gas condensate removal, miscible gas injection (huff 'n' puff), CO 2 injection, and thermal-EOR have been evaluated with the use of different NMR measurements (Adebayo et al 2020a, b;Chen et al 2018a, b;Dang et al 2019;Elsayed et al 2021bElsayed et al , 2020bHassan et al 2020;Mukhametdinova et al 2020). Drilling and production and engineering operation issues are also addressed in the literature.…”
Section: Introductionmentioning
confidence: 99%